Origin and evolution of qingke barley in Tibet - Xingquan Zeng (Nature Portfolio, 2018)
The origin of Tibetan barley (qingke) has been a controversial issue for many years. Here, the authors conduct population genomics study to support that qingke is derived from eastern domesticated barley instead of Tibetan wild barley and suggest southern Tibetan Plateau as its introduction route.